Adapted Phisical Activity for special populations with prader willi syndrome (original) (Revista científica Olimpia, 2020)
The research presented responds to the problem that arose during the work with people Prader Willi Syndrome and their families, where it was detected as a result of a diagnostic study that the physical activities promoted in the community do not respond to the characteristics, possibilities and potentialities of the special population group with SPW; that the technicians and professors of physical culture do not possess the knowledge to attend this population group; that the special population group with SPW is not integrated into physical activities because it presents as an essential motor characteristic a central hypotony that manifests itself in all stages of its life and that the families of the special population with SPW are interested in incorporating their children to community intervention programs to promote healthy lifestyles. Given the inadequacies in the psychopedagogical resources that technicians and specialists possess, to assume this process. The revealed causes point to the need to interrelate elements that functionally generate an integrating quality to assume the Adapted Physical Activity, rehabilitation and medical control, with adaptation to the personal profile of each disabled person, so it aims to: base the adaptations to perform the physical activity of the special population with SPW, in correspondence with their characteristics, possibilities and potentials for the promotion of healthy lifestyles in the community context. The study is carried out in the province of Ciego de Ávila, using the methodology of the case study, as a qualitative research strategy and from the complementarity of theoretical and empirical methods. The results achieved are revealed from the integration of these people to the practice of systematic physical activity, modification of their style and quality of life.